Estimation of phasors of power grid voltages and currents based on discrete samples of instantaneous values - Vasylets, Sviatoslav; Hlushchuk, Vladyslav (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
A method for estimating the real and imaginary parts of the phasor of voltages and currents of the power grid based on discrete readings of instantaneous values ​​is proposed. The method involves determining the projections on the complex axis of rotating phasors, which are calculated based on the discrete values ​​of signals corresponding to the instantaneous values ​​of phase voltages and currents. Rotating vectors are slowed down, which simplifies the analysis of phase shifts between them. The application of the proposed method will allow to increase the accuracy of detecting emergency modes, the reliability of protective shutdown, and the efficiency of electricity metering in a digital substation.